MICROFOSSILS AND RIPHEAN STRATIGRAPHY IN THE NORTH EUROPEAN PLATFORM (MEZEN SYNECLISE) - Veis A.F.; Vorob'eva N.G.; Fedorov D.L.; Kuzmenko Yu.T.; Golubkova E.Yu. (My University, 2004)
Microphytological remains from Riphean deposits of the Mezen syneclise (Leshukon depression) have been Eudied in 115 core samples characterizing in detail a sedimentary section penetrated by deep borehole Srednyaya Nyafta 21. The analyzed samples are from the depth interval of 4203-2080 m that spans the Safonovo Group and underlying lithostratigraphic subdivisions. The entire succession consists of the Vashka (4203-3647 m), Peza (3647-3090 m), Leshukon (2530-2134 m), and Nyafta (2134-1837 m) formations, the lowermost one distinguished for the first time (inappropriate facies of the Dorogor and Uftyug formations have not been sampled). Microfossils representing 27 species of 23 genera have been detected in 51 samples. The Riphean stratigraphy of Mezen syneclise is analyzed based on three successive microfossil assemblages distinguished in the section. Prevailing in the Vashka assemblage are the transit Riphean morphotypes Leiosphaeridia, Pterospennopsimorpha, and Nucellosphaeridium associated with more rare Navifusa and Spumosina. In addition to forms inherited from below, the Peza assemblage includes Chuaria, Polytrichoides, and Asperatofilum. The majority of Vashka and Peza taxa, as well as acanthomorphic acritarchs Trachyhystrichosphaera, Prolatoforma, and associated Pellicularia, Fabiformis, Ulophyton, and other forms represent the composite Safonovo assemblage. The facies-ecological affinity of established microphytological assemblages is as follows: the Vashka and Peza microfossils belong to shallow-water groupings, while the Safonovo assemblage seems to be of a deeper setting. The studied microfossils enable biostratigraphic correlation of their host deposits with the Riphean stratotype of southern Urals and with other representative Riphean sections of Siberia. As a result, the Vashka Formation is attributed to the Middle Riphean, and Peza Formation together with Safonovo Group is correlated with the Upper Riphean (according to other data, the Peza Formation spans the Yurmatinian interval). The pre-Vendian succession recovered by borehole Srednyaya Nyafta 21 and bearing microphytological remains can be regarded as the Riphean reference section in the north of the East European platform.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей